Sedimentary Organics in Glen Torridon, Gale Crater, Mars: Results From the SAM Instrument Suite and Supporting Laboratory Analyses. Issue 11 (12th November 2022) - Millan, M.; Williams, A. J.; McAdam, A. C.; Eigenbrode, J. L.; Steele, A.; Freissinet, C.; Glavin, D. P.; Szopa, C.; Buch, A.; Summons, R. E.; Lewis, J. M. T.; Wong, G. M.; et al.
Abstract: The Sample Analysis at Mars (SAM) suite instrument on board NASA's Curiosity rover has characterized the inorganic and organic chemical composition of seven samples from the Glen Torridon (GT) clay‐bearing unit. A variety of organic molecules were detected with SAM using pyrolysis (up to ∼850°C) and wet chemistry experiments coupled with evolved gas analysis (EGA) and gas chromatography‐mass spectrometry. SAM EGA and GCMS analyses revealed a greater diversity and abundance of sulfur‐bearing aliphatic and aromatic organic compounds in the sediments of this Gale crater unit than earlier in the mission. We also report the detection of nitrogen‐containing, oxygen‐containing, and chlorine‐containing molecules, as well as polycyclic aromatic hydrocarbons found in GT, although the sources of some of these organics may be related to the presence of chemical reagents in the SAM instrument background. However, sulfur‐bearing organics released at high temperature (≥600°C) are likely derived from Martian sources (e.g., igneous, hydrothermal, atmospheric, or biological) or exogenous sources and consistent with the presence of recalcitrant organic materials in the sample. The SAM measurements of the GT clay‐bearing unit expand the inventory of organic matter present in Gale crater and is also consistent with the hypothesis that clay minerals played an important role in the preservation of ancient refractory organic matter on Mars. These findings deepen our understanding of the past habitability and biological potential of Gale crater. Plain Language Summary: Organic molecules are essential to all life as we know it. Clay minerals are known on Earth for their high organic preservation potential and can be key indicators of past habitable environments. On Mars, the Glen Torridon (GT) region in Gale crater was first identified from orbit as a priority target for the Mars Science Laboratory mission due to its abundant clay minerals. To evaluate the organic preservation potential of this region, seven rock samples were collected and characterized using the Sample Analysis at Mars (SAM) instrument onboard the Curiosity rover. The SAM investigation indicated the presence of various organic compounds, including the first observation on Mars of some sulfur‐containing and ring‐structured organics and the highest abundance of sulfur organics observed to date. Our investigation of the sources of these organics revealed that while some of the sulfur‐bearing organics are likely Martian, a portion may also be related to the presence of chemical reagents carried in SAM, making attribution to a definitive source challenging. Nevertheless, these new SAM results confirm that ancient organic matter is preserved in the clay mineral bearing sediments of GT. Its origin—either meteoritic, abiotic or biotic—has yet to be established. Key Points: Curiosity explored the Glen Torridon region of Gale crater, which has a smectite‐rich mineralogy with high organic preservation potential The greatest diversity and abundance of sulfur‐bearing organics to date were detected in the solid samples by the SAM instrument S‐bearing organics extracted ≥600°C and some aromatic compounds likely come from martian refractory organic matter